(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the phonetic and lexical-stylistic changes in current Aruzian poems. It is necessary to specially research the basics of renewal. The weight of aruz, which applies to all genres of classical poetry, is closely related to the artistic thinking and the history of the art of words of our people, so it is always in the center of attention of poetic scholars. and is considered one of the urgent tasks. It is known that in the last years after independence, in a short period of time, special attention was paid to our historical and cultural heritage, and it was started to be studied on a deep scientific basis. In particular, using the creative freedom granted by independence, the traditions of our people were investigated in a historical-scientific aspect.